Notes on architectural education: An experimental approach to design studio - Ciravoglu, Aysen (ELSEVIER SCIENCE BV, 2014)
The aim of this paper is to share a new method in architectural design studio teaching. In order to overcome the problems related to the pedagogy of the architectural design studio, an experiment was conducted in both fall and spring semesters of the 20102011 academic year and fall semester of the 2011-2012 academic year in Architectural Design Studio 4 in Yildiz Technical University Faculty of Architecture, Istanbul. The process was designed to eliminate the pairing up of a single tutor and a student. Every week one single consultation and one group review where all of the studio teachers overviewed the projects together was constituted. After completion of the experiment, a questionnaire for both students and tutors was conducted. The paper presents the main findings of the questionnaire and discusses possible future scenarios of the architectural design studio. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: architectural education; design studio; pedagogy; responsibility; freedom; self-confidence; Education & Educational Research